Integrative Analysis of DNA Methylation and Transcriptome Identifies a Predictive Epigenetic Signature Associated With Immune Infiltration in Gliomas - Zhang, Jianlei; Yin, Jiang; Luo, Liyun; Huang, Danqing; Zhai, Dongfeng; Wang, Ge; Xu, Ning; Yang, Mingqiang; Song, Ying; Zheng, Guopei; Zhang, Qiong (Frontiers in Cell and Developmental Biology, 2021)
Gliomas is the most common primary brain tumor with poor prognosis and high mortality. The purpose of this study was to use the epigenetic signature to predict the prognosis and evaluate the degree of immune infiltration. We integrated gene expression profile and DNA methylation data of lower grade glioma and glioblastoma to explore the epigenetic differences and related biological function differences. Cox regression and lasso analysis were used to develop an epigenetic signature based on 8 DNA methylation sites to predict prognosis of gliomas patients. Kaplan-Meier analysis showed that the overall survival time of high- and low-risk groups was significantly separated, and ROC analysis verified that the model had great predictive ability. Besides, we constructed a nomogram based on age, gender, 1p/19q status, gliomas type, and risk score. The epigenetic signature was obviously associated with tumor purity, immune checkpoints, and tumor immune infiltrating cells (CD8+ T cells, gamma delta T cells, M0 Macrophages, M1 Macrophages, M2 Macrophages, activated NK cells, Monocytes, and activated Mast cells), so it may be used as a guide for the evaluation of immune infiltration or play a potential role in immunotherapy.